1992
DOI: 10.1088/0029-5515/32/2/i08
|View full text |Cite
|
Sign up to set email alerts
|

Plasma discharge fuelling by trimethylboron-a new wall conditioning technique

Abstract: A new in situ wall conditioning method by reactive gas fuelling has been investigated in TEXTOR; this method is applicable during plasma discharges of the operating machine. For these experiments, trimethylboron, B(CH3)3, was fed into the torus instead of hydrogen. While the hydrogen of the trimethylboron molecules fuels the plasma to sustain the discharge, boron and carbon are screened at the plasma edge and redeposited at the wall. The impurity concentration in the plasma is negligible, as it is after the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…During the fueling sequence, it was found that edge O and C luminosities were comparable to before TMB fueling, within the limited statistics, due to the initially clean conditions (Fig.3). Core oxygen was reduced, and as was found previously in larger aspect ratio tokamaks [10,11]. Edge fueling with the TMB mixture did not increase core B V and C VI for the close-wall NSTX geometry (Fig.3).…”
Section: Plasma Boronization: Fueling With 90%he and 10% Tmbsupporting
confidence: 85%
See 2 more Smart Citations
“…During the fueling sequence, it was found that edge O and C luminosities were comparable to before TMB fueling, within the limited statistics, due to the initially clean conditions (Fig.3). Core oxygen was reduced, and as was found previously in larger aspect ratio tokamaks [10,11]. Edge fueling with the TMB mixture did not increase core B V and C VI for the close-wall NSTX geometry (Fig.3).…”
Section: Plasma Boronization: Fueling With 90%he and 10% Tmbsupporting
confidence: 85%
“…It was found that the fraction of radiated power to total power during NBI fiducial discharges before and after the fueling sequence remained about the same at about 0.11. This is suggestive of the possible screening of the B and C components of TMB molecules discussed previously [10]. In addition, it was found that although the oxygen and carbon impurity levels decreased initially, and that the plasma performance continued to improve during the fueling sequences, these O and C luminosities remained relatively high.…”
Section: Plasma Boronization: Fueling With 100%tmbsupporting
confidence: 64%
See 1 more Smart Citation
“…Trimethylboron 41 and di-silane 42 have been injected into the SOL during tokamak discharges. Boron and silicon are redeposited on the walls while the hydrogenic atoms fuel the plasma with the same efficiency as deuterium gas, whereas the impurities are well shielded by the SOL from penetrating into hot plasma zones.…”
Section: Other Conditioning Methods Explored In Textormentioning
confidence: 99%
“…Plasma fueling with TMB had been tested previously on TEXTOR [6] and TdeV [7] and found to transport boron in the edge plasma to plasma wetted surfaces.…”
Section: * This Work Supported By Doe Contract No De-ac0276ch03073mentioning
confidence: 99%